Answer: A.3x² - 2x - 6
Step-by-step explanation:
complete question:
Jordan signed up for the Annual Cross Florida bike ride which is a 170 mile bike ride. After weeks of training he, rides at an average of 15 miles per hour. Write an equation that can be used to show Jordan's progress in miles (y) after a number of hours (x).
Answer:
y = 15x
Step-by-step explanation:
Jordan signed up for the annual cross Florida bike ride which is a 170 mile bike ride. He can rides at 15 miles per hours after series of training . The equation to express his progress in miles (y) after a number of hours (x) can be express below.
The question asked how much progress in miles after a number of hour. This is simply expressing an equation that show how much distance in miles he will cover after certain number of hour(s). The equation will be
y = 15x
15 times any hours he spent will give you Jordan progress in miles since his average is 15 miles per hour.
where
y = Jordan progress in miles
x = number of hours
Example his progress in miles after 2 hours will be as follow.
y = 15x
x = 2 hours
y = 15 × 2
y = 30 miles.
In this case his progress in miles after 2 hours according to the equation will be 30 miles .If he uses 3 hours his progress in miles will be 45 miles and so on .
Which system of equations can be used to solve this problem?
A. {c=150t
c=140t
B. {c=100−50t
c=80−60t
C.{c=100+50t
c=80+60t
D. {c=50+100t
c=60+80t
B. (0,0)
C. (0, 1)
D. X=0
Graph is attached , help quick please
Answer:
The answer is C.
Step-by-step explanation:
Inordertofindthesolutionofthelinearequation,youhavetofindthecoordinateswheretheyintersect.
So according to the graph, both lines intersect at the coordinates of ( 0 , 1 ).
(Correct me if I amwrong)
Answer:
To find the coordinates of x, we can use the midpoint formula, which says that the midpoint of a line segment is the average of the x-coordinates and the y-coordinates of the endpoints12. That is:
m=(2x1+x2,2y1+y2)
In this case, we know that m is (−3,−1) and y is (−8,6). We can plug these values into the formula and solve for x:
(−3,−1)−3−6x−1−2−8=(2x+(−8),2−1+6)=2x−8=x−8=2=2−1+6=−1+6=6
Therefore, x is (2,−8). You can check your answer by plugging it back into the midpoint formula and see if you get m.
I hope this helps
Step-by-step explanation: